Wawasan Buddhayana Sebagai Nilai Moderasi Beragama Dalam Spiritualitas Rohaniwan Sangha Agung Indonesia - Taridi Taridi; Ida Bagus Gde Yudha Triguna; Euis Dewi Yuliana (Jurnal Penelitian Agama Hindu, 2026)
The spiritual life of Buddhists should ideally be based on a deep understanding of universal Buddhist teachings. In the context of Buddhayana, the spiritual life encompasses not only theoretical aspects but also practical appreciation of non-sectarian values, inclusiveness, pluralism, universalism, and belief in Sang Hyang Adi Buddha. This study aims to analyse the factors that make the Buddhayana perspective important in the spiritual practice of Buddhist clergy in the Indonesian Sangha Agung. The study uses a qualitative approach with a case study method. Data was collected through interviews, observations, and documentation of a number of Buddhist clergy in the Indonesian Sangha Agung environment, then analysed inductively and thematically. The results of the study show that Buddhayana insights play an important role in shaping the personal transformation of clergy, encouraging dynamic and non-sectarian spiritual practices, and strengthening unity in the diversity of the sangha. This study confirms that the Buddhayana perspective is not only understood as a doctrine but also as an ethical conceptual framework that guides the spiritual practice and social role of clergy in a multicultural society. This study contributes academically to the study of contemporary Buddhism, particularly in the development of an integrative, moderate, and contextual model for clergy training.